Paradigmatic perspective for a quality improvement training programme for health professionals in the ministry of health and social services in Namibia - Amukugo, Hans Justus; Nangombe, Julia Paul (International Journal of Health, 2016)
This article focuses on the paradigmatic perspective facilitate the development of a quality improvement training programme for health professionals in the ministry of health and social services in Namibia. The study of this nature requires a paradigmatic perspective; this is a collection of logically linked concepts and propositions that provide a theoretical perspective or orientation that tends to guide the research approach to a specific. Assumptions are useful in directing research decisions during the research process.The study adopted a constructivism and interpretivism approach, since it involved understand the current situation of quality health care/service delivery at health care facilities, and explore and describe the of the health professionals; experiences at the health care facilities. The study was based on the specific information that was accepted as true, as obtained from those lived the experiences of challenges and constraints of providing quality health care at the health care facilities.The paradigm perspectives in this study include Meta – theoretical assumption which consisted ontological, epistemological, axiological, methodological and rhetorical assumptions. Theoretical basis of the study includes Dickoff (1968), Practice Oriented Theory; Programme development by Meyer and Van Niekerk; Kolb’s Theory of experiential learning; Demining’s model of quality improvement, Quality improvement policy of the Ministry of Health and Social Services (MoHSS) and Centre for Diseases control (CDC) framework for programme education.